The Effect of Multimedia Usage on Academic Achievement and Anxiety of Primary School Students - Hasan Çoruk, Recep Çakır (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2017)
This study aimed to investigate the effect of multimedia material covering 4th grade mathematics course fractions topic on students’ academic achievement levels, math anxiety, computer anxiety levels and thoughts on multimedia. A quasi-experimental design with pre-test - post-test and control group was conducted. The study was carried out with 31 students in each group: 13 male and 18 female students in the experimental group and 12 male and 19 female students in the control group. “Fractions Achievement Test”, “Mathematics Anxiety Scale”, “Computer Anxiety Scale”, and “Interview Form” were used as data collection tools. It was concluded that multimedia applications were more effective than traditional teaching methods in terms of improving academic achievement. According to the math anxiety data, neither multimedia applications nor traditional teaching methods were effective in relieving math anxiety of the students. The anxiety existing before the study was significantly reduced. The analysis of the interview forms indicated that multimedia applications helped students in some areas such as effective presentation, revising the subjects, increasing the interest in the course and providing a fun study environment. Multimedia applications were recommended to be used effectively in other courses as well in terms of lesson presentation, course revision and educational games.